Analisis Pendapatan Penyadap Aren di Desa Wali Kecamatan Watopute dan di Desa Wansugi Kecamatan Kabangka Kabupaten muna - Dewi, Sandra; Taridala, Sitti Aida Adha; Abdullah, Weka Gusmiarty (Department of Agribusiness, Halu Oleo University, 2018)
This research aims were to determine income of aren tappers in the research location. This research was conducted on September 2016 until May 2017 in Wali Village of Watopute Sub District and Wansugi Village of Kabangka Sub District at Muna District.Determination of the location in this study was conducted purposively of deliberately with the consideration that the two villages are the aren sap producing are with the different utilization of aren sap. The population in this research was the whole of aren sap tappers in Wali Village of Watopute Sub District at Muna District which the total numbers of 112 people and the processor of aren sugar in Wansugi Village at Kabangka Sub District which 11 people. Sampling technique in the Wali Village was done by the Simple Random Sampling technique with the sampling as much as 25 percent that were 28 people from population number. Sampling technique in theÂ Wansugi Village was done by the census sampling technique so that the number of samples was equal to the number of population that was 11 people. The result of the research showed that income of kameko processor higher than aren sugar processor